ENVIRONMENTAL RACISM IN CHILE - Meza-Lopehandía, Matías (Revista de Historia Social y de las Mentalidades, 2011)
The work concludes that we are in front of the ris ing of a new type social actor, that  it emerge from the contradictions of the neoliberal Chile that link it Ìs vindications to the  defense of the territory and the peoples right to t heir self-determination.
Keywords: Environmental racism; Public and private companies; Original people